DINAMIKA KELOMPOK DALAM PROSES EMERGENCY DECISION MAKING (EDM): PEMBELAJARAN DARI SIMULASI TANGGAP DARURAT DI PEMBANGKIT LISTRIK TENAGA NUKLIR: Lessons from Simulation Technique for Emergency Response in Nuclear Power Plants - Ratri Atmoko (Jurnal Perkotaan, 2020)
Nuclear Power Plant (NPP) is a non-fossil energy source with very high output and most sustain power plant. NPP is also classified as environmentally friendly because, in normal processes, NPP produces zero Carbon Dioxide (CO2) as the primary air pollutant. However, if there is a disaster, the impact is exceptionally terrible. Besides causing fatalities, it can also result in hazardous health problems and takes hundreds of years to recover the surrounding natural environment. Therefore, to avoid disaster, the skills of nuclear power plant operators are critical, especially in overcoming the crisis. Typical challenges in Analog System-based NPP is the synergy among operators whose numbers are higher than in digital systems. This paper reflects learning outcomes from simulation to overcome the crisis in NPP, particularly the immediacy in making the right decisions. The simulation was carried out at the Analog System-Based NPP Simulation Center in Essen, Germany, and followed by a group of students from the Human Factor Engineering Master Program, Hochschule Niederrhein, with diverse national cultural backgrounds. One result is that the unique characteristics of each nation's cultural background can affect its effectiveness in overcoming the crisis. Two different aspects are initiative and assertive behavior among people inside the group.